Financial Development and Tax Revenue in Developing Countries: Investigating the International Trade and Economic Growth Channels - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2019)
This study examines the effect of financial development on non-resource tax revenue performance in developing countries, including through the international trade and economic growth channels. Using a sample of 104 developing countries over the period 1980-2014, the empirical analysis shows that financial development exerts a positive effect on non-resource tax revenue performance. Interestingly, this positive effect takes place through higher trade openness, greater export product diversification, higher share of manufactured exports in total export products, and higher economic growth rate.
Keywords: F14; G20; H20; 330; Non-resource tax revenue; financial development; trade openness; export product diversification; manufacturing exports; economic growth